La innovación como estrategia para competir en los mercados dinámicos. - Acosta Castillo, Valeria Michelle; Vega Morejon, Bryan Andres (My University, 2020)
Globalization and the dynamism of markets pressure companies to implement different strategies to defend their position. Innovation stands out as a strategic response from companies to adapt to change. This work is guided by the objective of identifying the types of innovation that companies are adopting as strategies to compete in dynamic markets. A qualitative approach is used by applying theoretical historical-logical and analytical-synthetic methods for the interpretation of the relevant literature. Twenty scientific publications are used as sources of information covering case studies of exporting companies that have applied organizational practices, from which a type of innovation is associated. In the case of Ecuador, the analysis focuses on three productive sectors, taking as a reference the representativeness of export products. Among the main findings is that companies apply open innovation associated with certification processes that require external reference of good practices, cooperation and information transfer. Finally, it is concluded that the majority of firms employ incremental innovation, followed by open innovation and radical innovation to respond to changes in the environment, improve learning and take advantage of global market opportunities.
La globalización y el dinamismo de los mercados presionan a las empresas a implementar diversas estrategias para defender su posicionamiento. La innovación sobresale como respuesta estratégica de las empresas para adaptarse a los cambios. Este trabajo se guía por el objetivo de identificar los tipos de innovación que las empresas están adoptando como estrategias para competir en los mercados dinámicos. Se emplea un enfoque cualitativo mediante la aplicación de los métodos teóricos histórico-lógico y analítico-sintético para la interpretación de la literatura relevante. Se utilizan como fuentes de información 20 publicaciones científicas que cubren estudios de casos de empresas exportadoras que han aplicado prácticas organizacionales, a partir de las cuales se asocia a un tipo de innovación. Para el caso de Ecuador el análisis se centra en tres sectores productivos, tomando como referencia la representatividad de los productos de exportación. Entre los principales hallazgos se destaca que las empresas aplican la innovación abierta asociada a los procesos de certificación que requieren referentes externos de buenas prácticas, cooperación y transferencia de información. Finalmente se concluye que las empresas emplean mayoritariamente la innovación de tipo incremental, seguida de la innovación abierta y la innovación radical para responder a los cambios del entorno, mejorar el aprendizaje y aprovechar las oportunidades de los mercados globales.
Keywords: STRATEGY; COMPETITIVENESS; INNOVATION